Humanitarian assistance and disaster relief in the perspective of Indonesia Defense Policy - Samudro, Eko G.; Widana, I Dewa Ketut Kerta; Subiyanto, Adi; Mayori, Ersha (Technium Social Sciences Journal, 2022)
The development and progression in humankind’s understanding of the world and life, ensured a continuous evolution in the response to events threatening our livelihoods. Humankind also developed techniques to deal with natural hazards, either by aiming to contain the forces of nature, or by altering human own behavior. The humanitarian assistance and disaster relief are crucially important in order to protect the nations. This research employed literature review method. The results showed that every nation should prepare and manage their capabilities in Humanitarian Assistance and Disaster Relief (HADR), both in protection for own countries or in providing aids for the others. Military Operation Other Than War (MOOTW) does not involve the use or threat of violence but prioritizes the provision of HADR. In MOOTW, military forces synergize with other institutions/organizations, especially those related to diplomacy, economy, government, even politics and religion. Moreover, in handling disasters, especially in Indonesia, the combination between civilians and the military is crucial in realizing Civil-Military Cooperation (CIMIC) and Civil-Military Coordination (CMCoord). Under certain mechanism, the military power is only used to support civilian institution in HADR.